2013
DOI: 10.1177/0044118x13495053
|View full text |Cite
|
Sign up to set email alerts
|

“Somebody Who Was on My Side”

Abstract: Youth initiated mentoring (YIM) is an innovative approach to mentoring being implemented by the National Guard Youth ChalleNGe Program in which youth identify and select their mentors. There is great interest in this approach; however, there has been little study of YIM or its implementation in ChalleNGe. Retrospective in-depth qualitative interviews with former ChalleNGe participants (n = 30) were conducted to gain a descriptive understanding of the mentor selection process, the role these relationships playe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…In addition to previous qualitative research on the YIM approach (Schwartz et al, 2013; Spencer et al, 2016, 2018), our findings highlight the importance of the positioning process to become a YIM. The findings suggest what professionals call the natural paradox : How can professionals intervene to optimize relationship quality of the natural mentoring relationship without professionalizing this relationship too much?…”
Section: Conclusion and Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…In addition to previous qualitative research on the YIM approach (Schwartz et al, 2013; Spencer et al, 2016, 2018), our findings highlight the importance of the positioning process to become a YIM. The findings suggest what professionals call the natural paradox : How can professionals intervene to optimize relationship quality of the natural mentoring relationship without professionalizing this relationship too much?…”
Section: Conclusion and Discussionsupporting
confidence: 67%
“…The YIM approach can be considered as a hybrid approach integrating formal and informal care, in which the focus is on empowering the adolescent’s network through the positioning of and collaboration with an informal mentor, designated as a YIM. This informal mentor is a person (e.g., relative, neighbor, or friend) adolescents nominate from their own social network, who functions as a confidant and spokesman for the adolescent, and as a cooperation partner for parents and professionals (Schwartz et al, 2013; Spencer, Tugenberg, Ocean, Schwartz, & Rhodes, 2016; Van Dam et al, 2017). In the context of youth with complex needs, the mentor (or: YIM) works with family members and the professional team to increase or take advantage of the already existing resilience of the youth and family, and thereby improves their functioning (Van Dam & Verhulst, 2016).…”
Section: Natural Mentoring Integrated In Youth Mental Health Carementioning
confidence: 99%
See 1 more Smart Citation
“…Although these youths deviated from communal norms, by virtue of having left the accepted educational framework, the relationship they had with their mentor may have acted as an ongoing bridge between them and the community. Spencer et al (2016) found that mentors who came from within the youths’ communities were viewed by dropouts as expediting the development of feelings of trust, and contributing to the relevancy and meaningfulness of the guidance and advice offered. For youths at this stage of the dropout process, therefore, the relationship with a mentor from inside the community may have served as the one “good and meaningful youth-adult relationship” that, according to the literature, is enough to promote a youth’s healthy development (Luthar, 2006; Masten, Burt, & Coatsworth, 2006; Masten, Obradovic, & Burt, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Unsurprisingly, among the marked characteristics of at-risk youth is low self-esteem (Jessor, Turbin, & Costa, 1998; Metz, 2006), which has been associated with a lack of success in integrating into adaptive frameworks such as school or the workplace (Aristilde, 2006; Dillon, 2004). Having a mentor was found to be correlated with a greater likelihood of reporting relatively high levels of self-esteem (DuBois & Silverthorn, 2005; Spencer, Tugenberg, Ocean, Schwartz, & Rhodes, 2016).…”
Section: Personal Social and Psychological Aspects Of Youths’ Livesmentioning
confidence: 99%